Insight Transformed: Coming to Terms with Mindfulness in South Asian and Global Frames. (1st August 2018) - Stuart, Daniel
Abstract : This article fills in a gap in the historiography of modern insight and mindfulness meditation. By providing an account of the role of S. N. Goenka in the formation and dissemination of modern insight meditation (vipassanā), and his reframing of Burmese Buddhist meditation in a postcolonial South Asian context, I show how the roots of modern therapeutic forms of mindfulness emerge from magico-religious contexts that have been glossed over in a process of scientization. By presenting two parallel case studies from South Asia, in which insight meditation was appropriated and repurposed by Jain and Hindu communities under the pressure of distinct social, personal, and religious forces, I suggest that modern therapeutic mindfulness is just one instantiation of other similar processes. By understanding the variety of ways in which insight meditation has been encountered by and made available to prospective practitioners in multiple social and historical contexts, historians can better understand the complex of factors that gave rise to the modern category of 'mindfulness'.